Material Forming ESAFORM 2012 - Merklein, Marion; Hagenah, Hinnerk (2012)
Description: This two-volume set of technical articles on materials science represents the proceedings of the Fifteenth Conference of the European Scientific Association for Material Forming held in Erlangen, Germany during March, 2012. Volume is indexed by Thomson Reuters CPCI-S (WoS). The 227 peer-reviewed papers are grouped into the chapters: Keynotes; Formability of Metallic Materials; Forging and Rolling; Composite-Forming Processes; Semi-Solid Processes; Lightweight Design and Energy Efficiency in Metal Forming; New and Advanced Numerical Strategies for Material Forming; Extrusion and Drawing; Friction and Wear in Material Processing; Nano-Structured Materials and Microforming; Inverse Analysis Optimization and Stochastic Approaches; Constitutive Models for Metallic Alloys (Multiscale and Continuum); Innovative Joining by Forming Technologies; Incremental and Sheet-Metal Forming; Sheet-Bulk-Metal Forming; Heat Transfer Modelling; Structures, Properties and Processing of Polymers; Non-Conventional Processes; Machining and Cutting; Integrated Design, Modelling and Reliability Assessment in Forming (I-DMR
Keywords: Aluminum (Al); Anisotropy; Bending; CompositeM; Damage; Extrusion; Finite Element; Finite Element (FE) Simulation; Finite Element Method (FEM); Formability; Friction; Friction Stir Welding (FSW); Incremental Forming; Modeling; Numerical Simulation; Sheet Metal; Sheet Metal Forming; Sheet-Bulk-Metal Forming; Simulation; Yield Function